COMPARISON OF CONTACT LENS HYGIENE COMPLIANCE AND SELF-MANAGEMENT BEHAVIOURS BETWEEN MEDICAL AND NON-MEDICAL STUDENTS - Nisar, Dr. Sumera; Rehman, Areeb; Alqhtani, Shehanah Salem; Alrowibah, Hiba Abdualrahman; Mohammed, Fatimah F.; Alqahtani, Hala Maed; Aldulhum, Anfal Mohammed (Pakistan Journal of Physiology, 2018)
Background: Contact lenses are commonly worn by young population for many purposes such as vision correction, cosmetic causes and as a fashion trend. It can cause serious eye infections and corneal ulcers, sometimes resulting into loss of vision. The aim of study was to compare the contact lens hygiene compliance and self-management behaviour between medical and non-medical students of Saudi Arabia. Methods: Five hundred (500) young contact lens wearers with an age range of 18–28 years were selected conveniently from student population of Princess Nourah Bint Abdulrahman University, Riyadh. After taking informed consent from the participants, their level of contact lens hygiene compliance and self-management was assessed by using a peer-reviewed questionnaire. Results: The mean age of the participants was 21±2 years. Out of 500 students, 38% were medical and 62% were non-medical students. Fifty-six percent (56%) students were wearing contact lens for cosmetic reasons while 44% students were using it for the correction of their myopic refractive error. The self-management behaviour was statistically significant among non-medical students (p=0.026). There was no significant difference between the two groups regarding the compliance of the contact lens hygiene but the knowledge and awareness about the risks and complications was statistically high in the medical students (p=0.028). Conclusion: Self-management with contact lens use was very common among non-medical students of Saudi Arabia. They were good in lens hygiene compliance, but their knowledge about risks and complications of contact lens use and accessories care was significantly low. Pak J Physiol 2018;14(2):11–4